Actors, interactions, ties, and networks: the 'doing' of talent identification and development work in elite youth football academies. (4th July 2022) - Thomas, Ryan; Hall, Edward Thomas; Nelson, Lee; Potrac, Paul
ABSTRACT: The Premier League's Elite Player Performance Plan (EPPP) has transformed the ways in which young players are recruited, coached, supported and evaluated. To date, our scientific understanding of talent identification and development processes has been largely informed by (post)positivist studies addressing the physiological, psychological and biomechanical features of elite youth performance. In this paper, Crossley's relational theorising is presented as a heuristic device that could allow us to systematically recognise the interdependencies, ties, dialectics, and co-constituted interactions that comprise talent identification and development activities in professional football. We argue that his thesis enables us to better understand both a) the configuration and meaning making of those that comprise these relational networks, and b) the enabling and constraining features of (inter)action for these interconnected actors. For us, such knowledge can ultimately support the generation of accounts of talent identification and development that better reflect their inherently social, interactive and practical complexity.